Strategi pengembangan coto manggala sebagai pangan khas Kalimantan Tengah - Ervina Mela; Aulia Putri Wardhani; Mustaufik Mustaufik; Laeli Budiarti (AGROINTEK, 2023)
Coto Manggala is a cassava (manggala) soup originating from Pangkalan Bun, West Kotawaringin. This food has represented the region in certain events, such as the Anugerah Pesona Indonesia 2020, and received a MURI record in 2009. However, many modern foods that have entered Indonesia have shifted from traditional foods. This research aims to determine the level of satisfaction and consumer interest, select the attributes that need improvement, and formulate strategies for improving Coto Manggala products. In this study, there are three research stages: analyzing the satisfaction level and consumer interest, analyzing the attributes that need to be improved using IPA, and determining the strategy for improving Coto Manggala. It was found that the attributes that need to be improved are the ease of finding products and promotions in social media. For the ease of finding products, the improvement strategy has been set are collaborating with cassava suppliers and carrying out the right cassava storage system, registering the business on Google Maps so it is easier to be found, maximizing delivery services, selling products at a touristic location and starting the night culinary tourism, proper storage of finished foodstuffs, collaborating with Government agencies if there are cultural events that require Coto Manggala dishes, open booths when there are cultural events, join the exhibitions, etc. The improvement strategy for promotional attributes through social media is to maximize existing features on social media for product promotion, training and mentoring of MSME owners, and product branding